Handbook of energy audits - Thumann, Albert (Fairmont Press ; Distributed by Taylor & Francis, 2013)
This book is the most comprehensive and practical reference available on energy auditing in buildings and industry. Topics include energy assessment and computer software which will guide you in planning and carrying out a thorough and accurate energy audit of any type of facility, including electrical, mechanical and building systems analysis. Clear, easy-to-follow instructions guide you through accounting procedures, rate of return and life cycle cost analysis. Also covered is information on understanding your utility bill and using that knowledge to trim your energy costs. Loaded with forms, checklists and handy working aids, book is required reading for anyone responsible for conducting or overseeing a facility energy audit. Completely edited throughout, this latest edition includes a new chapter on investment grade energy audits and also a new chapter on retro-commissioning and energy audits. Revisions include new information on ISO 50001 and the Superior Energy Performance program plus a completely updated chapter on software. -- Provided by publisher.
Includes index.
Keywords: Energy auditing -- Handbooks, manuals, etc.; elektronické knihy; electronic books